Cerita Rakyat Anak Durhaka Ojuang Dan Pemanfaatannya Untuk Menyusun Bahan Ajar Teks Apresiasi - Ratmiati, Ratmiati; Antoni, Sri (Jurnal Bahasa Indonesia Prima (BIP), 2024)
This study aims to examine the folklore of the disobedient child Ojuang in Riau and its use to compile teaching materials for appreciation texts in vocational schools. This study is qualitative and uses descriptive methods. Description and analysis were carried out on the structure of the folklore of the disobedient child Ojuang, which consists of an analysis of the structure of the folklore. The results of this study are as follows: First, the plot or events that build the story use the law of cause and effect. Second, the main character is played by the child (Ojuang), this character is told quite a lot from beginning to end. The mother and father play other characters. Third, the setting in this story is divided into three parts, namely, the setting of place, the setting of time, and the setting of atmosphere. Fourth, the story of the occurrence of the folklore of the disobedient child Ojuang has a theme about a disobedient child. Disobedience is a trait that is not commendable, so the mother prays to God so that God will teach her child a lesson who does not want to acknowledge his mother. Fifth, the message in this story is (a) to be grateful to God Almighty. (b) Not to forget the services of both parents in any situation and condition. Sixth, the use of folk tales as teaching materials for compiling appreciation texts